1985
DOI: 10.1523/jneurosci.05-04-00866.1985
|View full text |Cite
|
Sign up to set email alerts
|

Lesions in nucleus basalis magnocellularis and medial septal area of rats produce qualitatively similar memory impairments

Abstract: The functional contribution of nucleus basalis magnocellularis (NBM) and the medial septal area (MSA) to memory was evaluated in two different spatial discriminations. Preoperatively, rats were trained to a criterion level of performance in a simultaneous left/right discrimination on the stem of a T-maze (a trial-independent memory) and a discretetrial, rewarded alternation discrimination on the arms of the T-maze (a trial-dependent memory). Bilateral lesions were made by injecting ibotenic acid (IBO) into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
88
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 382 publications
(104 citation statements)
references
References 30 publications
15
88
1
Order By: Relevance
“…Lesions of the fimbria-fornix, or electrolytic or neurotoxic lesions of the medial septum, impair hippocampal-dependent learning and memory (Mahut 1972;Olton et al 1978;Mitchell et al 1982;Rawlins and Olton 1982;Hepler et al 1985;Kelsey and Landry 1988;Markowska et al 1989;Kelsey and Vargas 1993). These studies have been interpreted as supporting the hypothesis that hippocampal ACh is necessary for normal memory function.…”
Section: Lesions Of the Medial Septum Or Its Projectionsmentioning
confidence: 86%
“…Lesions of the fimbria-fornix, or electrolytic or neurotoxic lesions of the medial septum, impair hippocampal-dependent learning and memory (Mahut 1972;Olton et al 1978;Mitchell et al 1982;Rawlins and Olton 1982;Hepler et al 1985;Kelsey and Landry 1988;Markowska et al 1989;Kelsey and Vargas 1993). These studies have been interpreted as supporting the hypothesis that hippocampal ACh is necessary for normal memory function.…”
Section: Lesions Of the Medial Septum Or Its Projectionsmentioning
confidence: 86%
“…Numerous neurochemical studies using both animals and humans have revealed age-related changes in neu rotransmitter enzyme activities and receptor binding (1)(2)(3)(4). Age-related memory disorders, including Alzhei mer's disease, show a substantial decrease in cholinergic markers, such as choline acetyltransferase (ChAT), acetyl cholinesterase (AChE) and the number of muscarinic receptors (mAChR), in the hippocampal formation and other cortical and basal forebrain structures (5-9).…”
mentioning
confidence: 99%
“…Ibotenic acid lesion of the nucleus basalis and/or medial septum, which include a num ber of cholinergic neurons projecting to the cortex and hippocampus, respectively, has been reported to produce a decrease in choice accuracy using this T-maze alternation task (19,(22)(23)(24). A similar memory decline was observed in rats that received an intracer ebroventricular injection of AF64A, a cho linergic neurotoxin (25).…”
Section: Discussionmentioning
confidence: 68%